How effective do economic growth in countries translate into remittance growth? an analysis of the Philippines remittance flows - Co, Johann Christian J. (School of Economics, University of the Philippines Diliman, 2019)
This paper seeks to understand economic performances in host countries translate into growth in remittances for recipient countries. By analyzing the determinants of remittance flows of Overseas Filipino Workers (OFW) to the Philippines, and extrapolating effect of external economic shocks on remittance flows, this paper uses oil prices as a factor to test the sensitivity of remittance flows to exogenous shocks. After categorizing the data to oil and non_oil producing OFW destination countries, a Vector Autoregression (VAR) function and an Orthogonal Impulse Response function (IRF) is employed to test the cumulative effects of multivariable relationships on GDP growth, remittances, and oil prices. Despite empirical results being largely statistically insignificant due to shocks being possibly dependent on primary driving factors, our analysis shows a growth in GDP of migrant host countries will potentially translate to a growth in remittances to the migrant homes countries.